Utilisation of Lactiplantibacillus plantarum and propionic acid to improve silage quality of amaranth before and after wilting: fermentation quality, microbial communities, and their metabolic pathway - Zhao, Muqier; Bao, Jian; Wang, Zhijun; Sun, Pengbo; Liu, Jingyi; Yan, Yuting; Ge, Gentu (Frontiers in Microbiology, 2024)
The aim of this study was to investigate the effects of Lactiplantibacillus plantarum (L. plantarum) and propionic acid (PA) on fermentation characteristics and microbial community of amaranth (Amaranthus hypochondriaus) silage with different moisture contents. Amaranth was harvested at maturity stage and prepared for ensiling. There were two moisture content gradients (80%: AhG, 70%: AhS; fresh material: FM) and three treatments (control: CK, L. plantarum: LP, propionic acid: PA) set up, and silages were opened after 60 d of ensiling. The results showed that the addition of L.plantarum and PA increased lactic acid (LA) content and decreased pH of amaranth after fermentation. In particular, the addition of PA significantly increased crude protein content (p < 0.05). LA content was higher in wilted silage than in high-moisture silage, and it was higher with the addition of L. plantarum and PA (p < 0.05). The dominant species of AhGLP, AhSCK, AhSLP and AhSPA were mainly L. plantarum, Lentilactobacillus buchneri and Levilactobacillus brevis. The dominant species in AhGCK include Enterobacter cloacae, and Xanthomonas oryzae was dominated in AhGPA, which affected fermentation quality. L. plantarum and PA acted synergistically after ensiling to accelerate the succession of dominant species from gram-negative to gram-positive bacteria, forming a symbiotic microbial network centred on lactic acid bacteria. Both wilting and additive silage preparation methods increased the degree of dominance of global and overview maps and carbohydrate metabolism, and decreased the degree of dominance of amino acid metabolism categories. In conclusion, the addition of L. plantarum to silage can effectively improve the fermentation characteristics of amaranth, increase the diversity of bacterial communities, and regulate the microbial community and its functional metabolic pathways to achieve the desired fermentation effect.